CLASS STRUGGLE IN 1984 BY GEORGE ORWELL - Mandai, Disyela Apriswa; Astuti, Rengganis Elung Naafi; Ekayani, Ridha; Nurholis, Nurholis (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
This article researches the complicated class structure of George Orwell's dystopian masterpiece, which is the novel titled "1984." By examining the clear and stark divisions within Oceania's society, this analysis aims to uncover the underlying social commentary that is on the text. The article will be focusing on two different classes, the classes are Bourgeois and Proletarian. Through a close examination of these classes' roles, privileges, and oppression, this study will reveal how Orwell makes use of class stratification to give a critique about the dangers of totalitarianism and the annihilation of individual freedom. This research will also focus more on showing the correlation and difference between the Bourgeois and Proletarian class, and how unfair the treatment the lower class will get meanwhile the higher class having a decent life. Ultimately, this exploration shows the lasting relevance of "1984" as a warning tale about the consequences of unchecked power and the timeless struggle for social justice.